2013
DOI: 10.3109/10715762.2013.845295
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin suppresses nitric oxide production in glial cultures by pro-inflammatory cytokines through p38 MAPK inhibition

Abstract: Melatonin has been shown to down-regulate inflammatory responses and provide neuroprotection. However, the mechanisms underlying the anti-inflammatory properties of melatonin are poorly understood. In the present work, we studied the modulatory effect of melatonin against pro-inflammatory cytokines in glial cell cultures. Treatment with pro-inflammatory cytokines mainly tumor necrosis factor-alpha, interleukin 1-beta, and interferon-gamma induces an increase in inducible nitric oxide synthase (iNOS) expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Moreover, several studies showed inhibition of iNOS expression by melatonin in various cell types. [41][42][43] Our results indicate that melatonin protects against the nitrooxidative damage on IECs and suggest that this protection may involve not only the known scavenging activity of melatonin against peroxynitrite 44 but also its ability to reduce NO release.…”
Section: Melatonin Inhibits Induced No Release From Stimulated Cacomentioning
confidence: 61%
See 1 more Smart Citation
“…Moreover, several studies showed inhibition of iNOS expression by melatonin in various cell types. [41][42][43] Our results indicate that melatonin protects against the nitrooxidative damage on IECs and suggest that this protection may involve not only the known scavenging activity of melatonin against peroxynitrite 44 but also its ability to reduce NO release.…”
Section: Melatonin Inhibits Induced No Release From Stimulated Cacomentioning
confidence: 61%
“…Although the NO scavenging activity of melatonin is known, the effects of melatonin on the levels of nitrite in the cell medium of stimulated Caco‐2 cells should be the consequence of iNOS downregulation. Moreover, several studies showed inhibition of iNOS expression by melatonin in various cell types …”
Section: Resultsmentioning
confidence: 99%
“…Melatonin suppressed MUC5AC production via the inhibition of Erk phosphorylation in EGF‐stimulated H292 cells. Additionally, the suppressive effects of melatonin on MAPKs phosphorylation have been previously described in many other reports . Based on these evidences, the pharmacological effects of melatonin involve the inhibition of MAPKs phosphorylation and melatonin is considered to have therapeutic potential for MAPKs‐related inflammatory pulmonary diseases, such as chronic bronchitis and pneumonitis induced by bacteria.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, NO levels were linked to neural precursor cell (NPC) survival and cell fate determination [49], that is, elevated levels of NO suppress NSC proliferation and enhance differentiation of NPCs into astrocytes [50, 51]. Melatonin is a hormone synthesized in the pineal gland [52] with indirect antioxidant abilities through induction of antioxidant enzymes [53] and inhibiting NO production in glial cultures through p38 inhibition [54]. It has been shown to protect NSCs against lipopolysaccharide- (LPS-) induced inflammation [52].…”
Section: Neural Stem Cells (Nscs)mentioning
confidence: 99%